2021
DOI: 10.3389/fpsyg.2021.636914
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Life Satisfaction: An Empirical Study in a Population of Senior Citizens

Abstract: Objective: The specialised literature indicates that the two key aspects in active ageing are performing physical activity and life satisfaction. Regarding physical activity, this not only improves physical aspects of senior citizens, but also has a positive impact on mental well-being and satisfaction with one’s own life. The aim is to demonstrate the relationship between these two variables to explain healthy ageing.Method: In a sample of 300 senior citizen subjects, the influence of various sociodemographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In some cases, there are significant differences between individuals in the physical and cognitive state of the elderly [ 3 ], which leads to the loss of cognitive and physical abilities. Life satisfaction and physical activity are two key aspects of healthy aging [ 4 ]. Life satisfaction of the elderly is the concrete embodiment of subjective well-being and healthy aging [ 5 ], and the theoretical basis for the development of healthy aging and the implementation of the healthy China strategy in China.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, there are significant differences between individuals in the physical and cognitive state of the elderly [ 3 ], which leads to the loss of cognitive and physical abilities. Life satisfaction and physical activity are two key aspects of healthy aging [ 4 ]. Life satisfaction of the elderly is the concrete embodiment of subjective well-being and healthy aging [ 5 ], and the theoretical basis for the development of healthy aging and the implementation of the healthy China strategy in China.…”
Section: Introductionmentioning
confidence: 99%
“…PA in older adults should be considered as one of the main strategies to promote health and prevent diseases, especially cognitive impairment [5,49,50]. In this regard, evidence suggests that older adults with higher levels of PA tend to have higher cognitive reserve scores and experience less cognitive impairment [16,18]. Iso-Markku et al [51] further demonstrated the protective effects of PA, highlighting the buffering role in the presence of mild cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in older adults, PA has been shown to reduce social isolation and improve quality of life [13,14] and cognitive function; it is also associated with positive changes in brain electrical activity [9]. Furthermore, studies have shown that older adults with higher cognitive, physical, and motivational reserves have less cognitive decline [15], and that there is a relationship between PA and cognition [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wagg et al (2021) considered subjective well-being, physical health, self-rated health, biological aging, and cognitive function as components of healthy aging [ 8 ]. Wobbeking Sanchez et al (2021) believed that the two key aspects of healthy aging are physical activity and life satisfaction [ 25 ]. Lara et al (2013) selected the components of healthy aging from five domains, including (i) physiological and metabolic health, (ii) physical capability, (iii) cognitive function, (iv) psychological wellbeing, and (v) social wellbeing [ 26 ].…”
Section: Literature Reviewmentioning
confidence: 99%